500 years of illustration from Albrecht Dürer to Rockwell Kent - Simon, Howard (Mineola, N.Y. Dover Publications, 2011)
"An unrivaled treasury of the methods, techniques, and examples of the great illustrators, this volume covers five centuries of decorations for the printed page. Ranging from the dawn of printing to the twentieth century, it offers working artists and students an unsurpassed reference and source of inspiration. It also forms a delightful browsing book for lovers of art and illustrated books.
Starting with 16th-century woodcuts by Albrecht Dürer and Hans Holbein, the chronological presentation features works by Goya, Hogarth, Blake, Morris, Doré, Toulouse-Lautrec, Beardsley, and other masters. A brief text introduces each section, and the volume concludes with an international roster of modern artists, categorized by country. All that is best and outstanding in the field of illustration appears here, in this giant book of sketches, engravings, woodcuts, and lithography. "--
Part One: The Past--
In the Beginning--
Albrecht Dürer--
Hans Holbein the Younger--
William Hogarth--
William Blake--
Francisco Jose; de Goya y Lucientes--
Thomas Bewick--
Thomas Rowlandson--
George Cruikshank--
Phiz--
John Leech--
Randolph Caldecott--
John Tenniel--
Sir William Schwenk Gilbert--
Aubrey Beardsley--
William Morris--
Edward Calvert--
Charles Henry Bennett--
Adrian Ludwig Richter--
Adolph Menzel--
Honore; Daumier--
Henri Toulouse-Lautrec--
Gustave Dore;--
Part Two: The Present--
Modern France--
Modern Germany--
Modern Poland--
Modern Russia--
Modern Italy--
Modern Belgium--
Modern Holland--
Modern Mexico--
Modern Great Britain--
The United States--
Includes index
Originally published: 500 years of art & illustration. Cleveland [Ohio] : World Pub. Co., 1942.
Keywords: Illustration of books; Illustrators